Argentine convertibility : is it a relevant precedent for the dollarization process in Ecuador? - Calcagno, Alfredo (ECLAC SantiagoCL, 2001)
Identifies the effects that the convertibility system has had on the Argentine economy, especially on growth ( both to rate and its instability), on the balance of payments and the foreign indebtness, on the structure of relative prices, and on the functioning of the banking system.